Implementasi Pendidikan Karakter Disekolah Melalui Pembiasaan Membaca Kalamun (Papadang Ati) Sebelum Mulai Belajar - hayatun nufus; Dina Indriana (Jurusan Pendidikan Bahasa Arab Fakultas Tarbiyah dan Keguruan Institut Agama Islam Negeri Sultan Maulana Hasanuddin, 2019)
This research was conducted with the aim of understanding the implementation of character education in shaping the personality of students. In this study using qualitative research methods. This research was conducted at SMAN 6 Pandeglang. Data is obtained by indept interview Based on the results of the study, it can be concluded: (1) that the implementation of education can be done by reading the kalamun (papadang ati) every morning. (2) religious and intelligent characters can be formed with this implementation.